THE INFLUENCE OF ORGANIZATIONAL ACTIVITIES ON MEDICAL STUDENTS’ ACADEMIC ACHIEVEMENT - Yolanda Ayu Yashinta; Budi Utomo; Fundhy Sinar Ikrar Prihatanto (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2018)
Background: The influence of extracurricular activities on academic achievement has been studied in several studies. Some studies support that extracurricular activities can negatively impact academic achievement but other studies emphasize the positive effects of extracurricular activities. Extracurricular activities discussed in this study is the activity of organizing students as measured by organizational activities and committees. The purpose of this study is to determine the effect of organizational activity measured by organizational activities and the committees that are followed by students on academic achievement.Method: Cross-sectional study, using questionnaires distributed to 221 medical students class of 2014 in medical faculty of Airlangga University.Results: This research was analyzed multivariate using R program by using logistic regression test to know the influence of independent variable to dependent variable. From the results of this study found that the organizational activity measured from the student organization and committee activities have no significant effect on academic achievement.Conclusion: organizational activities and committees play an important role in predicting the activity of organizing students, but from the results of this study found that the organizational activity measured from student organizations and committee activities have no significant effect on academic achievement.